Analisis Bauran Pemasaran Dalam Upaya Meningkatkan Penjualan Pada Perusahaan Distributor Tinta PT. X Di Cikarang Selatan - Dyah Harianti; Abbas Mansyur; Bertadi Nurseno (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This purpose of research to know and analyze marketing mix provide distributor PT. X about increase level in sales, to know and analyze of the risk constraints PT. X, and analyze of the solution PT. X for improve sales. This research use by kualitatif methode with the type of deskriptif research with by data collection technique as Interview and observation. The results showed that the application of the marketing mix applied by PT. X is quite effective, by holding promotions, products sold have increased annually by 137.36%. in terms of product and distribution the customer is quite satisfied, in terms of price and promotion there are differences so that using Triangulation where the application of prices and promotions applied by the company has differences according to the company's cooperation and the number of purchases, in the last 2 few years was sales's increased of 103,89%, the constraints in sales's gain is restriced of company's environment limited in marketing of product because of pandemic Covid-19 and company have to follow goverment's regulation, stock limited